The Role of Educational Leadership in Improving Teacher Performance and Learning Quality in the Digital Era - Afifah Maharani; Mah Sunah (JIEM (Journal of Islamic Education Management), 2026)
This study examines the role of educational leadership in improving teacher performance, staff professionalism, and the quality of learning in the digital era. The discussion focuses on two leadership models transformational and adaptive—which are considered the most relevant in addressing rapid changes in modern educational management. This research employs a literature review method by analyzing scientific sources related to leadership, educational management, and technology-based learning. The findings show that transformational leadership plays a crucial role in inspiring and motivating teachers, fostering innovation, and encouraging continuous professional growth. Meanwhile, adaptive leadership enables school leaders to understand complex changes, distinguish between technical and adaptive challenges, and mobilize teachers to respond more independently to the demands of the Merdeka Curriculum and digital learning. The combination of both leadership models effectively builds a collaborative school culture that is open to change and oriented toward improving learning quality. Thus, effective leadership serves as a fundamental pillar for schools in navigating educational transformation in the digital era.